PERAN KONSELOR PADA PENANGANAN ANAK BERKEBUTUHAN KHUSUS - Yosefa Efrida Angelina Manur; Rahmah Safitri; Niesha; Melinda Resvi; Sri Mulyanto; Rapita Wulansari; Romiaty Romiaty (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to examine the role of counselors in assisting children with special needs through a literature review approach. The method used is a literature review with content analysis techniques to identify, analyze, and synthesize various relevant previous research findings. Data sources were obtained from scientific journals, books, and academic publications discussing the concept of children with special needs and guidance and counseling services. The results of the study indicate that counselors play an important role in supporting the development of children with special needs in personal, social, academic, and career aspects. In the personal aspect, counselors help with emotional regulation, increasing self-confidence, and fostering independence. In the social aspect, counselors contribute to improving interaction skills and environmental adaptation. In the academic field, counselors assist in overcoming learning difficulties and optimizing students’ potential, while in the career field, counselors guide future planning based on the child’s interests and abilities. The forms of support provided include individual and group counseling services, collaboration with teachers and parents, and the development of programs tailored to the child’s needs. These roles have an impact on improving independence, social skills, discipline, and overall self-confidence of children with special needs. Keywords: Intervention, Special Needs, Counselor support.   Abstrak: Penelitian ini bertujuan untuk mengkaji peran konselor dalam mendampingi anak berkebutuhan khusus (ABK) melalui pendekatan studi literatur. Metode yang digunakan adalah literature review dengan teknik analisis isi untuk mengidentifikasi, menganalisis, dan mensintesis berbagai hasil penelitian terdahulu yang relevan. Sumber data diperoleh dari jurnal ilmiah, buku, dan publikasi akademik yang membahas konsep ABK serta layanan bimbingan dan konseling. Hasil kajian menunjukkan bahwa konselor memiliki peran penting dalam mendukung perkembangan ABK pada aspek pribadi, sosial, akademik, dan karir. Dalam aspek pribadi, konselor membantu pengelolaan emosi, peningkatan kepercayaan diri, dan kemandirian. Pada aspek sosial, konselor berperan dalam meningkatkan kemampuan interaksi dan adaptasi lingkungan. Dalam bidang akademik, konselor membantu mengatasi kesulitan belajar dan mengoptimalkan potensi siswa, sedangkan dalam bidang karir, konselor membimbing perencanaan masa depan sesuai minat dan kemampuan anak. Bentuk dukungan yang diberikan meliputi layanan konseling individu dan kelompok, kolaborasi dengan guru dan orang tua, serta penyusunan program sesuai kebutuhan anak. Peran tersebut berdampak pada peningkatan kemandirian, kemampuan sosial, kedisiplinan, serta kepercayaan diri ABK secara menyeluruh. Kata Kunci: Penanganan, Anak Berkebutuhan Khusus, Dukungan Konselor.